An alteration in ELMOD3, an Arl2 GTPase-activating protein, is associated with hearing impairment in humans. - Thomas J Jaworek; Elodie M Richard; Anna A Ivanova; Arnaud P J Giese; Daniel I Choo; Shaheen N Khan; Sheikh Riazuddin; Richard A Kahn; Saima Riazuddin (PLoS Genetics)
Exome sequencing coupled with homozygosity mapping was used to identify a transition mutation (c.794T>C; p.Leu265Ser) in ELMOD3 at the DFNB88 locus that is associated with nonsyndromic deafness in a large Pakistani family, PKDF468. The affected individuals of this family exhibited pre-lingual, severe-to-profound degrees of mixed hearing loss. ELMOD3 belongs to the engulfment and cell motility (ELMO) family, which consists of six paralogs in mammals. Several members of the ELMO family have been shown to regulate a subset of GTPases within the Ras superfamily. However, ELMOD3 is a largely uncharacterized protein that has no previously known biochemical activities. We found that in rodents, within the sensory epithelia of the inner ear, ELMOD3 appears most pronounced in the stereocilia of cochlear hair cells. Fluorescently tagged ELMOD3 co-localized with the actin cytoskeleton in MDCK cells and actin-based microvilli of LLC-PK1-CL4 epithelial cells. The p.Leu265Ser mutation in the ELMO domain impaired each of these activities. Super-resolution imaging revealed instances of close association of ELMOD3 with actin at the plasma membrane of MDCK cells. Furthermore, recombinant human GST-ELMOD3 exhibited GTPase activating protein (GAP) activity against the Arl2 GTPase, which was completely abolished by the p.Leu265Ser mutation. Collectively, our data provide the first insights into the expression and biochemical properties of ELMOD3 and highlight its functional links to sound perception and actin cytoskeleton.